Prolapse of a large pedunculated uterine myoma. Issue 2 (15th February 2022) - Papapanagiotou, Ioannis K.; Stavros, Sofoklis; Vlachos, Dimitrios‐Efthymios; Migklis, Kyriaki; Papadatou, Konstantina; Papageorgiou, Dimitrios; Manouvelou, Stamo; Zikopoulos, Athanasios; Domali, Ekaterini; Drakakis, Peter; Rodolakis, Alexandros; Thomakos, Nikolaos
Abstract: We report a rare case of a large prolapsed pedunculated uterine myoma measuring 15 cm in its greater diameter. In order to make a surgical procedure safe and feasible, appropriate clinical predictors should be taken into account and pre‐ and intraoperative preparations be available to the surgeon's armamentarium. Abstract : We report a rare case of a large prolapsed pedunculated uterine myoma measuring 15 cm in its greater diameter. In order to make a surgical procedure safe and feasible, appropriate clinical predictors should be taken into account and pre‐ and intra‐operative preparations be available to the surgeon's armamentarium.